Individual- and institution-level predictors of the turnover intention of medical staff among rural primary medical institutions in Xinjiang Production and Construction Corps, China: a cross-sectional multi-level analysis - Lin, Taoyu; Li, Ye; Li, Yuanyuan; Guo, Wei; Guo, Xiaoying; Tang, Changmin (Frontiers in Psychology, 2023)
Background Primary medical staff (PMS) are the guardians of population health. However, their loss further worsens the shortage and uneven distribution of human health resources, which should be addressed immediately. This study aimed to investigate the current status of turnover intention of rural PMS in Xinjiang Production and Construction Corps (XPCC) in China and its influencing factors atthe individual and institutional levels to provide reliable baseline data for intervention strategies to protect valuable rural PMS. Methods Participants were recruited from rural public health institutions of the XPCC using a cross-sectional multistage sampling process. Data on participants’ turnover intention and individual- and institution-level indicators were obtained through standardized electronic questionnaires and statistical reports of regional health administrative departments. The key factors influencing PMS turnover intention were identified us ingunivariateandmulti-level logistic regression analysis. Findings Overall, 20.5% (447/2182) of participants reported turnover intention. Univariate analysis showed that the occurrence of turnover intention was significantly influenced by marriage, education, age, year of working, monthly income, human resource management practices (HRMP), job satisfaction, per capita served population (PCSP) and number of beds (p < 0.05). Multi-level logistic regression analysis showed that bachelor’s degree or above and intermediate professional title were closely related to the occurrence of turnover intention (p < 0.05), age 41–50 years old and above, high human resource management practice, and high job satisfaction effectively reduced the odds (p < 0.05). The odds of turnover intention increased by 37% (p < 0.10) for PMS in institutions with PCSP more than 250 people. In contrast, the odds of turnover intention decreased to 68% (p < 0.05) for PMS in institutions with more than 50 beds. Conclusion Government-run primary medical institutions face the risk of PMS turnover intention. From a personal perspective, the high-risk population fortheturnover intention was mainly the PMS with bachelor’s degrees or above and intermediate professional titles. The low-risk population was the PMS with aged over 40 years, a higher evaluation of human resource management practice, and job satisfaction. From the perspective of primary medical institutions, larger institutions can reduce the turnover intention of individuals, whereas the size of the service population has the opposite effect.